Study on the variation of carbon storage in the Chang-Zhu-Tan urban agglomeration in China based on topographic relief - Mi, Yi; Li, Sheng; Wu, Bo (Frontiers in Environmental Science, 2024)
IntroductionRegional carbon storage is a significant indicator of ecosystem service functions. Examining the impact of changes in land use on carbon stock in the Chang-Zhu-Tan urban agglomeration under different topographic reliefs is paramount for sustainable land resource utilization and realizing carbon peaking and neutrality goals.MethodsThis study focuses on the Chang-Zhu-Tan urban agglomeration, using the InVEST model in combination with land use data to explore the distribution pattern of land use change and carbon storage from the perspective of topographic relief.ResultsThe research results show that:(1) the optimal analysis window for topographic reliefs in the study area is 17 × 17, covering an area of 0.26 km², with an average topographic relief of 78.58 m. (2) Between 2000 and 2020, Cultivated land and forest land decreased by 592.27 km² and 421.5 km², respectively, while the built-up land area increased by 982.36 km². (3) Due to human activities, carbon stock in the study area showed a decreasing trend, with a total reduction of 13.37 × 106 tons over the past 20 years. (4) The distribution of carbon stock across topographic reliefs mainly exhibits low-value and moderate-value carbon stock concentrations in flat and slightly undulating areas. In contrast, moderately high-value and high-value carbon stock concentrations are concentrated in gently and moderately undulating areas.DiscussionThese research findings provide a scientific foundation for optimizing the spatial pattern of the study area and formulating carbon peak and carbon-neutral policies.